USULAN MODEL KEBIJAKAN PENGEMBANGAN KOLEKSI PERPUSTAKAAN FAKULTAS ILMU BUDAYA UNILAK - Mafar, Fiqru (Universitas Lancang Kuning, 2012)
This paper discuss about the model of collection development pilicy at Perpustakaan Fakultas Ilmu Budaya Universitas Lancang Kuning. In this model, collection development pilicy consist of ten items, there are visionary mission and goal of library, users, responsibility of collection development, funding, selection procedure, special collection, weeding, gift collection, partnership, and handling of complaints. I hope this model can assist librarian to development their collections.